EFL CLASSROOM AND LEARNERS PERCEPTION ON DIRECT TRANSMISSION SCAFFOLDING - Purnomo, Averina; Yuyun, Ignasia (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
This study explored the learners perception on the use of direct transmission and scaffolding in the EFL classroom through a semi-structured interview. In this study, the constructivist view was narrowed to scaffolding. The method used by the higher education in Indonesia was still dominated by the situation where the lecturer acted as the knowledge provider. However, some lecturers have let go of the control in the classroom and give the opportunity for the learners to explore more. In this situation, the lecturers job is to assist the students and provide help (scaffold) if it is necessary. This study also employed a pre-test and post-test as a part of triangulation data to see the result from another perspective. The findings showed that the learners claimed in understanding and remembering the lesson more in scaffolding. However, the test showed that the learners score improved more in direct transmission.